Five masters of international law : conversations with R.-J. Dupuy, E. Jimňez de Arčhaga, R. Jennings, L. Henkin and O. Schachter - Cassese, Antonio (Hart, 2011)
This book consists of interviews with five distinguished international lawyers from the UK, USA, Uruguay and France, conducted by the editor, Antonio Cassese, between 1993 and 1995. Each interview is preceded by a brief ''intellectual portrait'' of the interviewee. In his general introduction Cassese stresses that the interviews, all based on the same questionnaire, were intended to bring out not only the main ideas associated with each scholar in the fields of international law and international relations, but also his intellectual and philosophical background, his general outlook and his vie.